Transition metal atom doping of the basal plane of MoS2 monolayer nanosheets for electrochemical hydrogen evolution. Issue 21 (9th May 2018) - Lau, Thomas H. M.; Lu, XiaoWei; Kulhavý, Jiří; Wu, Simson; Lu, Lilin; Wu, Tai-Sing; Kato, Ryuichi; Foord, John S.; Soo, Yun-Liang; Suenaga, Kazu; Tsang, Shik Chi Edman
Abstract : A Co atom enhances the HER activity of monolayer MoS2 whereas a Ni atom exhibits the opposite effect on the same basal site. Abstract : Surface sites of extensively exposed basal planes of MoS2 monolayer nanosheets, prepared via BuLi exfoliation of MoS2, have been doped with transition metal atoms for the first time to produce 2D monolayer catalysts used for the electrochemical hydrogen evolution reaction (HER). Their HER activity is significantly higher than the corresponding thin and bulk MoS2 layers. HAADF-STEM images show direct proof that single transition metal atoms reside at the surface basal sites, which subtly modify the electro-catalytic activity of the monolayer MoS2, dependent on their electronic and stereospecific properties. It is found that these dopants play an important role in tuning the hydrogen adsorption enthalpies of the exposed surface S atoms and Mo atoms in HER. We report electrochemical testing, characterization and computational modelling and demonstrate that Co can significantly enhance the HER activity by the dominant Co–S interaction, whereas Ni substantially lowers the HER rate due to the Ni–Mo interaction at the same basal site. The two transition metal dopants show opposite doping behavior despite the fact that they are neighbors in the periodic table.